Z dziejów polonistyki szkolnej - działalność nauczycielska Cecylii Niewiadomskiej1855-1925 = A chapter from the history of polish language and literature teaching in secondary schools: the teaching activity of Cecylia Niewiadomska (1855-1925) - Słowiński, Lech (1922-2005) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Cecylia Niewiadomska was one of the leading educationists of the nineteenth and the twentieth centuries. She was born in 1855 in Warsaw. After having finished her secondary education and qualifying as a teacher she begen to work as a teacher of Polish Language and Literature in secret educational groups and private schools for girls. She was an active member in many social organizations in the territories of the Kingdom of Poland, the objective of which was the education of Polish children threatened with the loss of their national identity resulting from the activities of the foreign power, dominating that part of Poland. (The National League, The Polish and Lithuanian Women's Circle, The Society for Secret Teaching, The Society for National Education, The Polish School Mother Organization and others).
Keywords: Niewiadomska, Cecylia (1855-1925)